Mechanical And Thermal Properties Of Hydroxyapatite Filled Poly(Methyl Methacrylate) Composites. - W, S Chow; H, K Tay; A Azlan, A Azlan; Mohd Ishak, Z A (2008)

(untitled)
Poly(methyl methacrylate) (PMMA) filled with hydroxyapatite (HA) filler has been widely used in biomaterial application. Acrylic denture base material was prepared from PMMA filled with HA.